Enhanced Photocatalytic CO2 Reduction with Incorporation of WO3 Cocatalyst in g-C3N4-TiO2 Heterojunction - Yiting Huo; Zhen Wu; Yanhui Yang; Bin Dong; Zhidong Chang (Molecules)
To enhance the performance of photocatalytic CO2 reduction, the development of suitable cocatalysts represents an effective strategy. Cocatalysts can interact with photocatalysts to improve light absorption capabilities and facilitate the separation and transfer of photogenerated electrons and holes. Moreover, they provide highly active surface sites that promote the adsorption and activation of CO2, which leads to acceleration of photocatalytic reduction. Herein, WO3 is employed as a cocatalyst to promote the CO2 photoreduction performance of a g-C3N4-TiO2 heterojunction through a facile and scalable calcination method. In pure water, optimal WO3/g-C3N4-TiO2 (WCT) delivers high selectivity CO and CH4 formation of 48.31 µmol·g−1 and 77.18 µmol·g−1 in the absence of a sacrificial reagent and extra photosensitizer, roughly 13.9 and 45.7 times higher than that of g-C3N4-TiO2 (CT). WO3 can strongly interact with g-C3N4-TiO2 electronically, guiding electrons across the interface to the surface. The oxygen vacancies in WO3, as electron-enriched centers, not only enhance charge separation and form efficient charge transfer channels but also capture photogenerated electrons to suppress charge recombination. This strong interaction and oxygen vacancies in WO3 jointly improve photocatalytic CO2 reduction activity and selectivity, offering a feasible way to design efficient cocatalysts.